Kalibrasi dan Validasi Sensor pH E-201C-Blue dan TDS Meter V1 pada Sistem Hidroponik Otomatis Berbasis IoT di Aswana Hidroponik - Rahardjo, Mikha El Charisto; Baraga, Bernaditus Yordan; Joyopranoto, Vincensius Agung Wibowo; Mahendra, Christy (Prosiding Seminar Nasional Teknoka, 2025)
This study aims to calibrate and validate the pH E-201C-Blue sensor and TDS Meter V1 implemented in an IoT-based automatic hydroponic system at Aswana Hydroponic, Purwokerto. The calibration process was carried out using a multi-point method with standard buffer solutions (pH 4, 7, and 10) and TDS solutions ranging from 500 to 1500 ppm to achieve optimal accuracy. An ESP32 microcontroller was used as the main controller and data transmitter to a cloud-based monitoring dashboard. The results showed that after calibration, the sensor achieved high accuracy with a correlation coefficient (R2) above 0.98 and an average error below 5%. These findings indicate that low-cost commercial sensors can provide reliable performance in automated hydroponic system, supporting time efficiency and improving crop productivity at Aswana Hydroponic, Purwokerto.